2023
DOI: 10.1097/dad.0000000000002406
|View full text |Cite
|
Sign up to set email alerts
|

Random Skin Biopsy for Diagnosis of Intravascular Large B-Cell Lymphoma: A Case Report and Literature Review

Abstract: Background:Intravascular large B-cell lymphoma (IVLBCL) is a rare, aggressive B-cell lymphoma. The heterogeneity of its clinical symptoms makes it hard to be diagnosed. The diagnosis is followed by pathological examination of affected tissues and organs including skin, central nervous system, and bone marrow. Random skin biopsy (RSB) with high sensitivity and less invasiveness becomes a common method for diagnosis in suspected patients without skin lesions.Case report:We reported the case of a 67-year-old man … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…An additional study [27] concluded no utility in skin biopsy with normal LDH and sIL-2R less than 2000 U/mL. In a recent case report [28], a patient with increased LDH and CNS symptoms (negative imaging) was only diagnosed with IVLBCL after a random skin biopsy; this cautionary example highlights random skin biopsy utility. The conclusion from the literature is that adequate sampling (quantity and depth), paired with targeted biopsy (hemangiomas when available), has utility in the diagnosis of IVLBCL; however, a negative biopsy does not exclude this entity, particularly in the setting of the HPS variant [1].…”
Section: Diagnosticsmentioning
confidence: 99%
“…An additional study [27] concluded no utility in skin biopsy with normal LDH and sIL-2R less than 2000 U/mL. In a recent case report [28], a patient with increased LDH and CNS symptoms (negative imaging) was only diagnosed with IVLBCL after a random skin biopsy; this cautionary example highlights random skin biopsy utility. The conclusion from the literature is that adequate sampling (quantity and depth), paired with targeted biopsy (hemangiomas when available), has utility in the diagnosis of IVLBCL; however, a negative biopsy does not exclude this entity, particularly in the setting of the HPS variant [1].…”
Section: Diagnosticsmentioning
confidence: 99%